The impact of physical activity on the level of chromosome aberrations - Šošić Gordana M.; Varjačić Mirjana (University Educons, Faculty of Sports and Tourism, Novi Sad, 2015)
During the lifetime, people are constantly exposed to the chemicals and agents of exogenic and endogenic sources, which through reaction with a molecule of DNA can cause the damage of genomes and their instability. The formation of micronuclei is a consequence of chromosomal aberrations caused by the influence of different genetic and environmental factors. Micronuclei are cytoplasmic chromatin masses that look like small nuclei and can originate from whole or parts of chromosomes. Micronucleus test ( MN test ) is used to detect genotoxic effects of various chemical , physical or biological mutagens, as well as the test for determination of chromosomal instability in a variety of cell types. Micronucleus frequency is directly proportional to the degree of chromosomal aberrations. It has been shown that genome damage may occur as a result of environmental exposure to genotoxins and medical procedures, due to deficiency of micronutrients and under the influence of various lifestyles and genetic factors. Unbalanced diet, lack of physical exercise, lack of sleep and overwork contribute significantly to increased frequency of micronuclei. It was also shown that strenuous exercise causes DNA damage, which results in the formation of micronuclei. As a professional athlete conduct highly Intensive physical training, these populations are at risk for the development of genomic instability and carcinogenesis. A healthy lifestyle, the optimal intake of antioxidants and regular moderate physical activity significantly reduced the frequency of micronuclei, and contribute to the stability of the genome.